2017
DOI: 10.17576/gema-2017-1701-04
|View full text |Cite
|
Sign up to set email alerts
|

Penceritaan Digital dalam Pemerolehan Leksikal Bahasa Jepun (Digital Storytelling in Japanese Lexical Acquisition)

Abstract: ABSTRAKKajian ini merupakan kajian kes yang mengkaji proses pemerolehan leksikal bahasa Jepun melalui Penceritaan Digital (Digital Storytelling). Penceritaan Digital merupakan kaedah mencipta dan menyampaikan cerita dengan menggunakan peralatan teknologi. Matlamat kajian ialah untuk mengenal pasti strategi pemerolehan leksikal yang digunakan ketika pembikinan Penceritaan Digital dan menganalisis proses pemerolehan leksikal ketika pembikinan Penceritaan Digital. Seramai sembilan orang pelajar dari sebuah univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(4 reference statements)
0
2
0
2
Order By: Relevance
“…Evidently, many Arabic vocabulary games have been developed within various applications, such as Kahoot, Quizizz, and Wordwall. Salleh et al (2017) found that incorporating digital technology elements into learning can further facilitate the vocabulary acquisition process for students. Moreover, Kapp (2012) emphasizes that digital game-based learning can assist students in enhancing their experiences by stimulating a range of skills, including problem-solving, 21stcentury skills, and higher-order thinking skills (HOTS).…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, many Arabic vocabulary games have been developed within various applications, such as Kahoot, Quizizz, and Wordwall. Salleh et al (2017) found that incorporating digital technology elements into learning can further facilitate the vocabulary acquisition process for students. Moreover, Kapp (2012) emphasizes that digital game-based learning can assist students in enhancing their experiences by stimulating a range of skills, including problem-solving, 21stcentury skills, and higher-order thinking skills (HOTS).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, effective teaching methods will have a positive effect on pupils in understanding the vocabulary learned quickly and effectively. The use of digital technology themed elements is one of the good initiatives in promoting the process of vocabulary acquisition (Salleh et al, 2017). The choice of inappropriate and tedious teaching materials will affect the achievement of Arabic vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…La relación establecida marca-audiencia posibilita crear una comunidad de consumidores con gustos afines que están dispuestos a compartir sus experiencias en redes sociales, convirtiéndolos en prosumidores. Incluso, el uso de este tipo de narrativas permite a la audiencia entrar en un estado mental determinado e identificarse con la marca porque sus actitudes se ven afectadas debido a los estímulos que han recibido a través del visual storytelling (Chiang et al, 2018;Ferreira, 2009;Jany, 2000;Robin, 2008, como se cita en Salleh et al, 2017) 3 METODOLOGÍA La investigación de enfoque cualitativo presenta un paradigma interpretativo con un diseño fenomenológico que ayuda a comprender e interpretar las experiencias vividas por diferentes individuos en relación a un concepto en una situación particular (Ataro, 2020;Creswell, 2013). Para ello, se tiene como caso de estudio las fotos y videos que pertenecen a la campaña de lanzamiento del restobar Sastreía Martínez que se desarrolló en el feed de…”
Section: Relación De Categoríasunclassified
“…Sobre esta ruta, se puede mencionar que Sastrería Martínez podría ser el próximo top of mind pues, si comparamos Carnaval con Sastrería Martínez ambos están desarrollando acciones comunicacionales como el uso del visual storytelling que los ayuda a influir en la actitud de los usuarios. Este tipo de narrativas aportan estímulos que introduce a los consumidores en un estado mental determinado, ya que sus actitudes se ven afectadas (Chiang et al, 2018;Ferreira, 2009;Jany, 2000;Robin, 2008, como se cita en Salleh et al, 2017). En ese sentido, la gran mayoría de informantes determinaron que el visual storytelling de la campaña de lanzamiento de Sastrería Martínez estaba ambientada en la época de la prohibición en Estados Unidos donde el consumo de bebidas alcohólicas era ilegal y, por ende, empezaron a crear bares clandestinos o speakeasies con la finalidad de seguir divirtiéndose (Merino, 2020).…”
Section: ) [I08]unclassified